Novel alpha 2 beta 1 Integrin Inhibitors Reveal That Integrin Binding to Collagen under Shear Stress Conditions Does Not Require Receptor Preactivation - Nissinen L; Koivunen J; Käpylä J; Salmela M; Nieminen J; Jokinen J; Sipilä K; Pihlavisto M; Pentikäinen OT; Marjamäki A; Heino J (AMER SOC BIOCHEMISTRY MOLECULAR BIOLOGY INC, 2022)
The interaction between alpha 2 beta 1 integrin (GPIa/IIa, VLA-2) and vascular collagen is one of the initiating events in thrombus formation. Here, we describe two structurally similar sulfonamide derivatives, BTT-3033 and BTT-3034, and show that, under static conditions, they have an almost identical effect on alpha 2-expressing CHO cell adhesion to collagen I, but only BTT-3033 blocks platelet attachment under flow (90 dynes/cm(2)). Differential scanning fluorimetry showed that both molecules bind to the alpha 2I domain of the recombinant alpha 2 subunit. To further study integrin binding mechanism(s) of the two sulfonamides, we created an alpha 2 Y285F mutant containing a substitution near the metal ion-dependent adhesion site motif in the alpha 2I domain. The action of BTT-3033, unlike that of BTT-3034, was dependent on Tyr-285. In static conditions BTT-3034, but not BTT3033, inhibited collagen binding by an alpha 2 variant carrying a conformationally activating E318W mutation. Conversely, in under flow conditions (90 dynes/cm(2)) BTT-3033, but not BTT-3034, inhibited collagen binding by an alpha 2 variant expressing E336A loss-of-function mutation. Thus, the binding sites for BTT-3033 and BTT-3034 are differentially available in distinct integrin conformations. Therefore, these sulfonamides can be used to study the biological role of different functional stages of alpha 2 beta 1. Furthermore, only the inhibitor that recognized the nonactivated conformation of alpha 2 beta 1 integrin under shear stress conditions effectively blocked platelet adhesion, suggesting that the initial interaction between integrin and collagen takes place prior to receptor activation.